A potential of using palm oil solid waste by-product (palm oil clinker and oil palm shell) as partial aggregate replacement - Amir Fadli, Abu Bakar (2012)
Palm oil clinker (POC) and oil palm shell (OPS) which is relatively low cost and abundantly available has the potential as a replacement for aggregates in the production of concrete. This study investigates the effects of substitution of palm oil clinker and oil palm shell aggregates towards the mechanical properties of porous concrete which consist of density and compressive strength. The most suitable water cement ratio for the mixture of porous concrete was obtained through mix design and yielded a constant of 0.57. Four types of samples were prepared with the constant w/c of 0.57 and POC content of 5% for all mixture and OPS content of 0%, 5%, 10% and 15% by the weight of crushed granite aggregates respectively. The result of this study indicates that the substitution of POC and OPS aggregates in concrete reduces the density of concrete. The higher porosity achieved through the addition of POC aggregates contributes to the reduction in density. However, the replacement of crushed granite aggregates with POC and OPS aggregates resulted in a drop in strength development. The result shows that the compressive strength of concrete reduced significantly. This study indicates that concrete with POC and OPS content can be utilized as lightweight concrete but cannot be used for load bearing purposes due to low strength.